The Relationship between Exclusive Breastfeeding and Infant Weight in Marekofo Village - Evi Muhammad; Anik Sri Purwanti (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Background: Exclusive breastfeeding (EBF) is a critical factor influencing infant growth and development. Adequate nutrition during the first six months of life supports optimal weight gain, immunity, and overall health. Despite recommendations from the World Health Organization (WHO) and the Indonesian Ministry of Health, not all mothers practice exclusive breastfeeding due to various social, cultural, and knowledge-related factors (Sari & Putri, 2022). Previous studies have indicated a significant relationship between exclusive breastfeeding and improved infant weight, highlighting the need for community-level interventions to support EBF practices (Rahmawati & Handayani, 2023). In Marekofo Village, there is limited data regarding the association between exclusive breastfeeding and infant weight, making this research important for local health planning and maternal education programs. Objective: This study aimed to examine the relationship between exclusive breastfeeding and infant weight in Marekofo Village.Methods: An analytical observational study with a cross-sectional design was conducted. A total of 30 infants aged 0–6 months and their mothers were selected as the sample using purposive sampling techniques. Data on exclusive breastfeeding status and infant weight were collected through structured interviews and direct measurement using standardized infant weighing procedures. The relationship between exclusive breastfeeding and infant weight was analyzed using the Wilcoxon signed-rank test, with a significance level of p < 0.05.Results: The results showed that 30 mothers (100%) practiced exclusive breastfeeding, and 20 infants (90%) had normal weight, while 10 infants (10%) had lower-than-expected weight. The Wilcoxon signed-rank test indicated a significant relationship between exclusive breastfeeding and infant weight (p = 0.000), suggesting that infants who were exclusively breastfed tended to have healthier weight outcomes.Conclusion: Exclusive breastfeeding has a significant positive effect on infant weight in Marekofo Village. These findings emphasize the importance of promoting exclusive breastfeeding practices through maternal education, community support, and health services to ensure optimal infant growth and development.